Des bonobos distinguent les braconniers des scientifiques - David Beaune (Revue de Primatologie)
Field studies on apes involve primate habituation process. However, the increasing poaching pressure could threaten the ape communities of animals habituated by humans. In this note, I relate how a group of bonobos (Pan paniscus) from LuiKotale Research Station (DR Congo) responded to encounter with poachers. Bonobos have not reacted as with researchers when encountering the group. They stopped their activities, took refuge in the canopy, observed the poachers' passage silently. This shows that bonobos can distinguish researchers from poachers and adapt their behavior to the dangerousness of the situation.